(untitled) (Journal of Medical & Health Sciences Review, 2025)
The increasing demand for high-quality poultry products accelerated the need for precise genetic improvement strategies beyond the limitations of conventional breeding. This study investigates the use of CRISPR/Cas9-mediated genome editing to improve the quality of eggs and meat in poultry by targeting key genes responsible for shell formation, muscle growth, nutrient composition, and immune response. Fertilized embryos were edited using designed guide RNAs and further validated through PCR and Sanger sequencing. Results showed an attainment of highly efficient editing, about 87.5%, with minimum off-target effects. Significant improvements in phenotype were unveiled, such as a 15% increase in the strength of eggshells, enhanced yolk quality, and increased egg size compared with controls. In addition, there were marked improvements in meat quality traits, including a 12% increase in muscle mass, 15% reduction in fat deposition, and 10% elevation in protein content. More so, the gene-edited birds revealed substantially higher disease resistance with a reduced number of mortalities under pathogen challenge. A strong linear correlation between gene expression and protein content further confirmed the functional impact of targeted modifications. However, the study has provided compelling evidence that the CRISPR/Cas9 technology can efficiently and safely modify poultry genomes to improve product quality and provides a transformative approach for future poultry breeding programs.